EFEKTIVITAS PEMBELAJARAN BAHASA INDONESIA SISWA KELAS XI SMA NEGERI 1 SUNGAI RAYA - Dela, Dela; Sulissusiawan, Ahadi; Heryana, Nanang (Universitas Tanjungpura, 2024)
The background of this study is the importance of the effectiveness of Indonesian language learning in class XI IPS. This study aims to describe the effectiveness of the teacher's role in learning, the effectiveness of the media used, and the readiness of all elements in learning Indonesian in Class XI IPS SMA Negeri 1 Sungai Raya. This research uses descriptive qualitative method. The data in this study came from Indonesian language teachers in class XI IPS SMA Negeri 1 Sungai Raya. Data collection techniques through observation, interviews, and documentation. Based on the results of the analysis on the effectiveness of Indonesian language learning, it can be seen that there are several roles of teachers for effective learning including teachers directing good things to students, guiding students according to the objectives of learning so that it runs smoothly, seeing the condition of students is ready or not, can manage the class well, and provide support to students. There are several media used in learning effectiveness, namely laptops, power point (PPT), canva, and videos. The overall readiness of elements such as preparing a Learning Implementation Plan (RPP) is made according to what is needed in the learning process.